Buddha image meditation is a potent predictor for mental health outcomes: A cross-sectional study among Thai high-school students - Justin DeMaranville; Tinakon Wongpakaran; Nahathai Wongpakaran; Danny Wedding (PLoS ONE, 2025)
Purpose Meditation has been demonstrated to benefit adolescent mental health. This research examined various meditation styles practiced in northern Thailand to determine which were associated with positive and negative mental health outcomes in adolescents. Population and methods High school students who were 15–18 years old and who were enrolled in grades 10–12 in either secular or Buddhist Thai boarding schools were recruited following their school’s willingness to participate. They provided information about meditation styles and their practice frequency during the last month (i.e., breathing, kasina (color), Buddha image visualization, Manomayiddhi, mindfulness, recollections, and vipassanā). The Rosenberg Self-Esteem Scale (RSES), Resilience Inventory (RI-9), Outcome Inventory-21 (OI-21), and Perceived Stress Scale (PSS-10) were completed. Multiple linear regression model analysis was used to identify the effects of meditation styles on mental health outcomes. Results Among 443 participants, 390 were females (87.9%). The mean age was 16.35 ± 0.96 years. The three most common meditation styles practiced were breathing, Buddha image visualization, and mindfulness (46.5%, 26.2%, and 22.8%, respectively). Buddha image visualization was a significant predictor of RSES (B = 1.69, 95%CI = 0.77, 2.61), RI-9 (B = 2.95, 95%CI = 0.68, 2.95), OI-Anxiety (B = −2.38, 95%CI = −3.34, −1.41), OI-Depression (B = −1.94, 95%CI = −2.64, −1.24), and PSS-10 (B = −2.47, 95%CI = −3.65, −1.28), whereas Manomayiddhi was a predictor of RI-9 (B = 2.47, 95%CI = 0.74, 2.47), OI-Anxiety (B = −2.32, 95%CI = −3.41, −1.23), OI-Depression (B = −1.53, 95%CI = −2.32, −0.74), and PSS-10 (B = −2.14, 95%CI = −3.46, −0.81). Breathing meditation predicted OI-Depression (B = −0.87, 95%CI = −1.45, −0.29). Daily meditation frequency was associated with the best mental health scores (p < 0.001). Conclusion Buddha image visualization, Manomayiddhi, and breathing meditation were predictive of adolescents’ mental health. A higher practice frequency is associated with positive mental health outcomes.